Rådgivarens vårdslöshet – Vårdslöshetsrekvisitet i rådgivningsavtal och förhållandet till det i andra uppdragsavtal - Hjelm,Elsa (2025)
Many companies need professional advice, for example from a lawyer or an accountant. It is often cheapest for companies to outsource such expertise, which is why they turn to companies that offer consulting services. The contract that arises between the parties is an advisory agreement, which is a type of intangible consultancy agreement. As consultancy agreements between commercial parties are largely unregulated by law, the culpa rule becomes the guiding principle when determining when an advisor may be liable for damages to their client. The culpa rule stipulates that a consultant is liable for damages to its ordering party on contractual grounds if it, with proximate cause, causes damage to the ordering party, either with intent or through negligence. The purpose of this thesis is to investigate the prerequisite of negligence expressed by the culpa rule in advisory agreements and how it relates to the prerequisite of negligence in other consultancy agreements. To achieve this purpose, a method of legal dogmatics is used to map the applicable law in the area and thus answer the questions posed in the thesis. Due to the limited number of applicable laws regulating these agreements, the thesis is based primarily on case law and legislative history. To supplement the sources of law, doctrine is also used. The prerequisite of negligence that applies to advisory agreements and that which applies to other consultancy agreements are compared, and the differences identified are subsequently discussed and questioned. The comparison is based on seven Supreme Court cases, three of which concern advisory agreements and four of which concern other consultancy agreements. These cases provide insight into the Supreme Court's assessment of due care, which determines whether the prerequisite of negligence has been met. The assessment of due care focuses primarily on the consultant's methodological responsibility and duty to provide information. The investigation shows that the prerequisite of negligence that applies to advisory agreements is more difficult to meet than that which applies to other consultancy agreements. In other words, it is easier for a consultant who is not an advisor to fulfil the requirement than it is for an advisor to do so. The differences found between the prerequisite of negligence in advisory agreements and that of other consultancy agreements are 1) the possibility for a consultant's negligence to be trumped by the ordering party's contributory negligence, 2) the scope of the duty to provide information, and 3) the interaction between the principles of loyalty and vigilance. After discussing these differences, the investigation concludes that some minor differences between the prerequisites may be justified in view of the special features of advisory agreements. That said, not all differences identified by the study are justified.
Keywords: avtalsrätt; skadeståndsrätt; rådgivning; uppdragsavtal; vårdslöshet; culpa; rådgivningsavtal; rådgivare